2021
DOI: 10.1002/app.50914
|View full text |Cite
|
Sign up to set email alerts
|

3D‐printed wood‐polylactic acid‐thermoplastic starch composites: Performance features in relation to biodegradation treatment

Abstract: In view of the current public concern about microplastics, biodegradability of 3D‐printed polymeric materials is an important issue. In this work, we studied the effects of soil‐burial biodegradation treatment on wood‐polylactic acid (PLA) blends with three different thermoplastic starch (TPS) contents (i.e., 0, 10, and 20 wt%). The wood‐PLA‐TPS composites were 3D‐printed through the fused deposition modeling technique. The use of TPS led to reduced mechanical properties and thermal stability of the composites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The activity of microorganisms initiates surface changes and allows access to the inner areas of the print, which promotes swelling and makes more space available in the composites. It has also been observed that the degree of filling of the material supports accelerated degradation [207]. Similar observations have been reported for PLA by adding rice hulls [208].…”
Section: Biodegradation Of Composites In Soil Environmentssupporting
confidence: 79%
“…The activity of microorganisms initiates surface changes and allows access to the inner areas of the print, which promotes swelling and makes more space available in the composites. It has also been observed that the degree of filling of the material supports accelerated degradation [207]. Similar observations have been reported for PLA by adding rice hulls [208].…”
Section: Biodegradation Of Composites In Soil Environmentssupporting
confidence: 79%
“…Moreover, because fibers such as lignocellulose are hydrophilic in nature, the addition of fillers containing these fibers accelerates the process of water absorption into biodegradable composites [16]. To date, only a few studies have been published on the negative impact of water on the mechanical properties of 3D-printed polymer materials, including factors such as the degree of crystallization, degree of infilling, and addition of natural fillers [17].…”
Section: Introductionmentioning
confidence: 99%
“…Composites made of PLA, wood, and TPS (corn starch) were examined for water absorption and biodegradation tests. [ 157 ] The authors created three distinct composites with varying TPS content (0%, 10%, and 20%). For TPS composites, glycerol was employed as a bidding agent.…”
Section: Fdm Compositesmentioning
confidence: 99%
“…[60] In past decades, the devolvement of new material called composite for FDM is increased because of its reasonable strength and durability. [61,67,144,157] However, composite materials fabricated through conventional manufacturing (Injection molding, RTM, compression molding, etc.) performed better than pure polymers.…”
Section: Inferences Based On the Mechanical Performance Of Fdm Natura...mentioning
confidence: 99%